Hybrid HfC‐SiCN matrix for improved oxidation resistance of carbon fiber–reinforced mini‐composites - Shakir Bin Mujib; Mohammed Rasheed; Saravanan R Arunachalam; Gurpreet Singh (International Journal of Ceramic Engineering & Science, 2024)
Abstract Hafnium carbide (HfC) is an ultrahigh‐temperature ceramic with high melting point, chemical stability, hardness, and wear resistance. However, its low fracture toughness and poor thermal shock resistance limit its structural applications in extreme environments. In this study, co‐curing of liquid precursors was carried out prior to complete pyrolysis of individual polymeric precursors. First, HfC preceramic polymer precursor was cured, followed by silicon carbonitride (SiCN) precursor curing on a 2D carbon fiber (CF) cloth using the drop‐coating process. The infiltrated CFs were pyrolyzed at 800°C to achieve CF/HfC‐SiCN ceramic mini‐composites. The cross‐linked precursor‐to‐ceramic yield was observed to be as high as 65% when the procedure was carried out in an inert environment. Although stable up to 1200°C, CF/HfC‐SiCN samples demonstrated susceptibility to oxidation at 1500°C in ambient air. The oxidation of HfC in the presence of SiC leads to the formation of a hafnium‐containing silicate (HfxSiyOz) along with hafnia (HfO2). This compound of silicate and hafnia limits oxygen diffusion better than SiO2 and HfO2 individually. The incorporation of SiCN in HfC ceramic led to improved phase stability compared to a neat HfC system. The results of this study also show that the use of liquid‐phase precursors for HfC and SiCN in the polymer‐infiltrated pyrolysis method is a promising approach to fabricating high‐temperature structural ceramic matrix composites with good oxidation resistance.